Composite dielectric material and preparation method and application thereof
By introducing an epoxy polymer shell on the surface of barium titanate and forming a covalent crosslinking structure with cyanoethyl cellulose, the problem of poor interfacial compatibility between barium titanate ceramic filler and polymer matrix is solved, and a composite dielectric material with high dielectric constant and low dielectric loss is achieved.
Patent Information
- Application Number
- CN202311172145.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2023-09-12
- Publication Date
- 2025-03-14
AI Technical Summary
The existing barium titanate ceramic filler has poor interfacial compatibility and easy agglomeration, resulting in defects inside the material and affecting its dielectric properties.
By introducing a polymer shell containing epoxy groups on the surface of barium titanate and forming a covalent crosslinking structure with the hydroxyl group in cyanoethyl cellulose, the compatibility and dispersion of the filler and the matrix are improved.
It significantly improves the dielectric properties of composite materials, has a high dielectric constant and low dielectric loss, enhances the mechanical properties of the materials, and effectively suppresses leakage and conduction current.
Smart Images

Figure CN119613819A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of dielectric materials, and in particular to a composite dielectric material and a preparation method and application thereof. Background Art
[0002] As an efficient storage and conversion device for intermittently generated sustainable energy, dielectric capacitors play an irreplaceable role in the field of new energy. The core of dielectric capacitors is dielectric materials with high energy storage density. Polymer dielectrics are ideal dielectric materials due to their advantages such as light weight, flexibility, and large-scale preparation. Common polymer dielectrics include biaxially oriented polypropylene (BOPP), polyester (PET), polyphenylene sulfide (PPS), and polyvinylidene fluoride (PVDF)-based polymers. Among them, BOPP has been widely used in dielectric capacitors as a commercial dielectric material. However, on the one hand, the dielectric constant of BOPP is low (~3), and the energy storage density is difficult to increase; on the other hand, the contradiction between resource consumption and environmental pollution is becoming increasingly prominent, and it is urgent to develop new sustainable materials to replace petrochemical-based materials.
[0003] Ceramic materials such as barium titanate (BT) and lead zirconate titanate (PZT) usually have high dielectric constants (>10 2 ), and compounding it with dielectric polymer materials is expected to obtain flexible dielectric polymer composite materials with excellent dielectric properties and insulation properties. However, the surface energy difference between ceramic fillers and polymer matrices is large, the dispersion uniformity and compatibility of ceramic fillers in polymer matrices are poor, and ceramic fillers are prone to agglomeration, resulting in poor compatibility of the filler-matrix interface and easy formation of defects at the interface. Under the action of an electric field, defects at the interface between the two phases will cause leakage current to rise, thereby reducing the dielectric properties of the material. Summary of the invention
[0004] The purpose of the present invention is to overcome the problems of poor interface compatibility, easy agglomeration and easy formation of defects inside the material between barium titanate ceramic fillers and polymer matrix in the prior art, and to provide a composite dielectric material and a preparation method and application thereof. The composite dielectric material has excellent dielectric properties, high dielectric constant and low dielectric loss.
[0005] In order to achieve the above-mentioned object, the first aspect of the present invention provides a composite dielectric material, the composite dielectric material comprising a filler and a matrix material, the filler is modified barium titanate, and the matrix material is cyanoethyl cellulose;
[0006] The modified barium titanate comprises a barium titanate core and a shell, wherein the shell comprises a polymer containing epoxy groups, and the core and shell are connected by covalent bonds. According to infrared spectrum test, the infrared spectrum of the modified barium titanate has a peak at 910±10cm -1、1720±10cm -1 There are characteristic peaks of epoxy group and carbonyl group respectively.
[0007] The modified barium titanate filler particles are introduced into the cyanoethyl cellulose matrix, so that the epoxy groups in the barium titanate shell layer react chemically with the hydroxyl groups in the cyanoethyl cellulose to form a covalent cross-linking structure.
[0008] The second aspect of the present invention provides a method for preparing a composite dielectric material, comprising: providing a dispersion liquid comprising a matrix material, a filler and an organic solvent, and then casting the dispersion liquid into a film and drying it;
[0009] The filler is modified barium titanate, and the matrix material is cyanoethyl cellulose;
[0010] The modified barium titanate comprises a barium titanate core and a shell, wherein the shell comprises a polymer containing epoxy groups, and the core and shell are connected by covalent bonds. According to infrared spectrum test, the infrared spectrum of the modified barium titanate has a peak at 910±10cm -1 、1720±10cm -1 There are characteristic peaks of epoxy group and carbonyl group respectively.
[0011] The modified barium titanate filler particles are introduced into the cyanoethyl cellulose matrix, so that the epoxy groups in the barium titanate shell layer react chemically with the hydroxyl groups in the cyanoethyl cellulose to form a covalent cross-linking structure.
[0012] The third aspect of the present invention provides the use of the composite dielectric material described in the first aspect or the composite dielectric material prepared by the preparation method described in the second aspect in a dielectric capacitor.
[0013] On the one hand, barium titanate (BT) is an inorganic ceramic particle with a high dielectric constant. It has excellent dielectric and insulating properties, but its interfacial compatibility with the polymer matrix is poor. The barium titanate filler is easy to agglomerate, resulting in defects inside the composite material, affecting its dielectric properties. On the other hand, compared with traditional polymer matrices that are difficult to degrade and non-renewable, cellulose, as a natural organic material, has abundant reserves and a wide range of sources. Highly substituted cyanoethyl cellulose (CEC) can be used as a potential candidate material for high-performance capacitors due to its high dielectric constant and small dielectric loss. However, due to the poor compatibility between cyanoethyl cellulose and existing inorganic fillers, the dielectric properties of the resulting composite dielectric material are difficult to achieve the expected goals.
[0014] The inventors of the present invention have found in their research that by introducing a polymer shell containing epoxy groups on the surface of barium titanate, the charge accumulation at the inorganic-organic interface can be effectively suppressed, the breakdown field strength can be increased, and the leakage current can be suppressed. At the same time, the epoxy groups in the modified barium titanate shell can react with the hydroxyl groups in cyanoethyl cellulose through covalent bonds to form a covalent cross-linked network. The cross-linked network acts as an electronic potential well, which can suppress the leakage current, improve the electric field strength and dielectric properties, and ultimately improve the energy storage density. At the same time, due to the covalent bonds formed between the filler and the matrix, the dispersibility and compatibility of the barium titanate filler in the matrix are significantly improved; in addition, the formation of covalent bonds also enhances the mechanical properties of the composite material, and as a dielectric material, it exhibits good dielectric properties, with a high dielectric constant and low dielectric loss. BRIEF DESCRIPTION OF THE DRAWINGS
[0015] Figure 1 is a TEM image of the modified barium titanate prepared in Preparation Example 1 of the present invention;
[0016] Figure 2 It is the Fourier transform infrared spectra of BT-OH, BT-APS, BT-Br and BT-g-PGMA-1 prepared in Preparation Example 1 of the present invention;
[0017] Figure 3 Thermogravimetric curves (TG) of barium titanate (BT), BT-Br and BT-g-PGMA-1 prepared in Preparation Example 1, BT-g-PGMA-2 prepared in Preparation Example 2, BT-g-PGMA-3 prepared in Preparation Example 3, and BT-g-PMMA prepared in Comparative Example Preparation Example 1;
[0018] Figure 4 (a) is a dielectric constant curve of the composite dielectric material prepared in Examples 1-4 of the present invention;
[0019] Figure 4 (b) is a dielectric loss curve of the composite dielectric material prepared in Examples 1-4 of the present invention;
[0020] Figure 4 (c) is a dielectric constant curve of the composite dielectric material prepared in Comparative Examples 2-5 of the present invention;
[0021] Figure 4 (d) is a dielectric loss curve of the composite dielectric material prepared in Comparative Examples 2-5 of the present invention;
[0022] Figure 5 (a) is the energy storage density and charge-discharge efficiency curve of the composite dielectric material prepared in Examples 1-4 of the present invention;
[0023] Figure 5(b) is the energy storage density and charge-discharge efficiency curve of the composite dielectric material prepared in Comparative Examples 2-5 of the present invention. DETAILED DESCRIPTION
[0024] The endpoints and any values of the ranges disclosed in this article are not limited to the precise ranges or values, and these ranges or values should be understood to include values close to these ranges or values. For numerical ranges, the endpoint values of each range, the endpoint values of each range and the individual point values, and the individual point values can be combined with each other to obtain one or more new numerical ranges, which should be considered as specifically disclosed in this article.
[0025] The first aspect of the present invention provides a composite dielectric material, the composite dielectric material comprising a filler and a matrix material, the filler is modified barium titanate, and the matrix material is cyanoethyl cellulose;
[0026] The modified barium titanate comprises a barium titanate core and a shell, wherein the shell comprises a polymer containing epoxy groups, and the core and shell are connected by covalent bonds. According to infrared spectrum test, the infrared spectrum of the modified barium titanate has a peak at 910±10cm -1 、1720±10cm -1 There are characteristic peaks of epoxy group and carbonyl group respectively.
[0027] In the modified barium titanate described in the present invention, the shell layer is connected to the barium titanate nanoparticles through a covalent bond to form an outer shell of a polymer containing epoxy groups. The present invention uses a polymer shell layer containing epoxy groups to functionally modify the barium titanate nanoparticles, as long as the shell layer includes a polymer containing epoxy groups. Small molecule segments can be introduced on the surface of the barium titanate first, so that it can participate in the polymerization reaction as a macromolecular initiator, and the modification method includes but is not limited to hydroxylation treatment of the barium titanate nanoparticles, treatment with a silane coupling agent containing terminal amino groups, and halogenation treatment of an acyl halide reagent. The functionally modified barium titanate can be used as a macromolecular initiator to initiate polymerization of polymers containing epoxy groups, so that they are coated on the surface of the barium titanate to form a polymer shell layer.
[0028] The inventors of the present invention have found in their research that by introducing a polymer shell containing epoxy groups on the surface of barium titanate, the charge accumulation at the inorganic-organic interface can be effectively suppressed, the breakdown field strength can be increased, and the leakage current can be suppressed. The modified barium titanate filler has good dispersibility and compatibility in the cyanoethyl cellulose matrix, and the composite dielectric material has a high dielectric constant and low dielectric loss. The reason is that the modified barium titanate shell contains epoxy groups, and the hydroxyl groups in the cyanoethyl cellulose, the epoxy groups in the modified barium titanate shell and the hydroxyl groups in the cyanoethyl cellulose can form a covalent bond connection, thereby improving the compatibility of the modified barium titanate filler and the cyanoethyl cellulose.
[0029] According to the present invention, preferably, based on the total mass of the modified barium titanate, the content of the shell is 5-20wt%, preferably 10-18wt%, for example, it can be 10wt%, 11wt%, 12wt%, 13wt%, 14wt%, 15wt%, 16wt%, 17wt%, 18wt% and other typical but non-limiting content values or the range between the two; the content of the barium titanate core is 80-95wt%, preferably 82-90wt%, for example, it can be 82wt%, 83wt%, 84wt%, 85wt%, 86wt%, 87wt%, 88wt%, 89wt%, 90wt% and other typical but non-limiting content values or the range between the two. The composite dielectric material with the above preferred composition is conducive to taking into account both high dielectric constant and low dielectric loss.
[0030] Preferably, the shell also includes a small molecule segment, which acts as a macromolecular initiator to participate in the polymerization reaction, triggering the polymerization of the polymer containing epoxy groups, so that it is coated on the surface of the barium titanate to form a polymer shell. Preferably, the small molecule segment is selected from the residue of a silane coupling agent containing an amino group and / or the residue of an acyl bromide.
[0031] Preferably, in the shell, the content of small molecule segments does not exceed 35wt%, preferably 18-30wt%; the content of polymers containing epoxy groups is not less than 65wt%, preferably 70-82wt%. In the above preferred composition, it is conducive to the formation of a covalent cross-linked network between the filler and the cellulose matrix.
[0032] In the present invention, the content of each component in the modified barium titanate is obtained by thermogravimetric analysis.
[0033] In the present invention, there is a wide range of selection for the specific type of the polymer containing epoxy groups, as long as it can provide epoxy groups.
[0034] In some preferred embodiments of the present invention, the polymer containing epoxy groups is polyglycidyl methacrylate (PGMA). PGMA has high polarity. In the above preferred case, it is beneficial to further improve the dielectric constant of the material. At the same time, as an insulating interface, it can effectively inhibit the charge accumulation at the inorganic-organic interface, increase the breakdown field strength, and inhibit the leakage current.
[0035] According to the present invention, preferably, the average particle size of the barium titanate is 10-100 nm, for example, it can be 10 nm, 15 nm, 20 nm, 25 nm, 30 nm, 35 nm, 40 nm, 45 nm, 50 nm, 55 nm, 60 nm, 65 nm, 70 nm, 75 nm, 80 nm, 85 nm, 90 nm, 95 nm, 100 nm, etc. Typical but non-limiting particle sizes. Further preferably, the average particle size of the barium titanate is 80-100 nm. In the above preferred case, it is conducive to the dispersion of the modified barium titanate in the matrix material.
[0036] According to the present invention, preferably, the degree of substitution of the cyanoethyl cellulose is 2-2.8, preferably, the degree of substitution of the cyanoethyl cellulose is 2-2.6. Selecting the above preferred combination of cyanoethyl cellulose and modified barium titanate is beneficial to ensure that the composite dielectric material has a higher dielectric constant, while ensuring that the cyanoethyl cellulose has appropriate hydroxyl groups that are not replaced by cyanoethyl groups, which is beneficial to improving the interface compatibility between the filler and the cyanoethyl cellulose and improving the mechanical properties of the composite material.
[0037] The present invention has a wide range of selection for the content of filler and matrix material in the composite dielectric material. According to some preferred embodiments of the present invention, based on the total mass of the composite dielectric material, the content of the filler is 5-20wt%, preferably 10-15wt%; the content of the matrix material is 80-95wt%, preferably 85-90wt%. In the above preferred case, it is beneficial to further improve the dielectric properties of the composite dielectric material.
[0038] The second aspect of the present invention provides a method for preparing a composite dielectric material, comprising: providing a dispersion liquid comprising a matrix material, a filler and an organic solvent, and then casting the dispersion liquid into a film and drying it;
[0039] The filler is modified barium titanate, and the matrix material is cyanoethyl cellulose;
[0040] The modified barium titanate comprises a barium titanate core and a shell, wherein the shell comprises a polymer containing epoxy groups, and the core and shell are connected by covalent bonds. According to infrared spectrum test, the infrared spectrum of the modified barium titanate has a peak at 910±10cm -1 、1720±10cm -1 There are characteristic peaks of epoxy group and carbonyl group respectively.
[0041] The definition of the modified barium titanate is the same as that of the composite dielectric material described above, and will not be repeated here.
[0042] According to the preparation method provided by the present invention, the epoxy group in the shell of the modified barium titanate and the hydroxyl group in the cyanoethyl cellulose can form a stable covalent bond connection during the composite process, thereby improving the compatibility of the modified barium titanate filler and the cyanoethyl cellulose. At the same time, the modified barium titanate and the cyanoethyl cellulose form a covalent bond so that the composite material forms a covalent cross-linked network, providing an electronic potential well that can effectively inhibit the migration of carriers, and the prepared composite dielectric material has a higher dielectric constant and lower dielectric loss.
[0043] In some preferred embodiments of the present invention, the preparation method of the modified barium titanate comprises:
[0044] (1) hydroxylating barium titanate;
[0045] (2) mixing the product obtained in step (1), a silane coupling agent containing a terminal amino group and a first solvent, and performing a silanization treatment;
[0046] (3) mixing the product obtained in step (2), an acyl halide and a base, and performing a surface functionalization treatment on the product obtained in step (2);
[0047] (4) Under light-induced conditions and in the presence of a catalyst, the product obtained in step (3) is mixed with a polymer monomer containing an epoxy group to carry out a reaction, wherein the reaction includes a grafting reaction and a polymerization reaction.
[0048] The present invention utilizes light-induced atom transfer radical polymerization technology to prepare modified barium titanate with a core-shell structure. Compared with heat-induced surface-initiated atom transfer radical polymerization, the amount of catalyst used can be greatly reduced, and the metal residue in the obtained product can be significantly reduced, which is beneficial to improving the application prospects of modified barium titanate in electrical materials.
[0049] According to a preferred embodiment of the present invention, the method for preparing the composite dielectric material comprises:
[0050] Providing a dispersion liquid including cyanoethyl cellulose, modified barium titanate and an organic solvent, and then casting the dispersion liquid into a film and drying it;
[0051] Wherein, the modified barium titanate is prepared by the following method:
[0052] (1) hydroxylating barium titanate;
[0053] (2) mixing the product obtained in step (1), a silane coupling agent containing a terminal amino group and a first solvent, and performing a silanization treatment;
[0054] (3) mixing the product obtained in step (2), an acyl halide and a base, and performing a surface functionalization treatment on the product obtained in step (2);
[0055] (4) Under light-induced conditions and in the presence of a catalyst, the product obtained in step (3) is mixed with a polymer monomer containing an epoxy group to carry out a reaction, wherein the reaction includes a grafting reaction and a polymerization reaction.
[0056] In the present invention, hydroxyl groups are introduced into the surface of barium titanate through the hydroxylation treatment described in step (1).
[0057] According to a specific embodiment of the present invention, the hydroxylation treatment in step (1) comprises: mixing barium titanate with hydrogen peroxide and performing a hydroxylation treatment.
[0058] Preferably, the hydroxylation treatment is carried out at a temperature of 80-120°C, preferably 95-110°C, and for a time of 2-8h, preferably 3-6h.
[0059] Preferably, the mass ratio of the hydrogen peroxide calculated as H2O2 to the barium titanate is 8-10:1, preferably 8.5-9.5:1.
[0060] The present invention has a wide selection range for the concentration of the hydrogen peroxide. Preferably, the concentration of the hydrogen peroxide is 20-40wt%, preferably 25-35wt%.
[0061] According to the present invention, preferably, the average particle size of the barium titanate is 10-100 nm, for example, it can be 10 nm, 15 nm, 20 nm, 25 nm, 30 nm, 35 nm, 40 nm, 45 nm, 50 nm, 55 nm, 60 nm, 65 nm, 70 nm, 75 nm, 80 nm, 85 nm, 90 nm, 95 nm, 100 nm, etc. Typical but non-limiting particle sizes. Further preferably, the average particle size of the barium titanate is 80-100 nm. In the above preferred case, it is conducive to the dispersion of the barium titanate filler in the matrix.
[0062] In the present invention, amino groups are introduced on the surface of barium titanate by using a silane coupling agent containing terminal amino groups through the silanization treatment in step (2). The present invention has a wide range of selection for the specific type of the silane coupling agent containing terminal amino groups, as long as the introduction of amino groups can be achieved.
[0063] According to a preferred embodiment of the present invention, the silane coupling agent containing a terminal amino group is selected from 3-aminopropyltrimethoxysilane and / or 3-aminopropyltriethoxysilane. The use of the above preferred silane coupling agent containing a terminal amino group is conducive to the next step of reacting with an acyl halide reagent to obtain a macromolecular initiator.
[0064] According to the present invention, in order to ensure that the silane coupling agent containing terminal amino groups fully reacts with the hydroxyl groups on the surface of barium titanate, preferably, in step (2), the temperature of the silanization treatment is 50-100°C, for example, it can be 50°C, 60°C, 70°C, 80°C, 90°C, 100°C and other typical but non-limiting temperatures, preferably 70-90°C; the time of the silanization treatment is 12-48h, for example, it can be 12h, 20h, 24h, 30h, 36h, 40h, 48h and other typical but non-limiting times, preferably 20-30h.
[0065] Preferably, the silanization treatment is performed under a protective atmosphere, and the protective atmosphere is provided by at least one of nitrogen, argon and neon.
[0066] In the present invention, the required range for the amount of the silane coupling agent containing terminal amino groups is relatively wide, as long as all the hydroxyl groups on the surface of barium titanate are converted into amino groups. Preferably, the mass ratio of the product obtained in step (1) to the silane coupling agent containing terminal amino groups is 1-3.5:1, for example, it can be 1:1, 1.5:1, 2:1, 2.5:1, 3:1, 3.5:1 and other typical but non-limiting ratios, preferably 2-2.5:1.
[0067] In the present invention, there is no particular limitation on the specific type of the first solvent, as long as it is conducive to dispersing the reactants. Preferably, the first solvent is xylene. The present invention also does not have a particular limitation on the amount of the first solvent, and those skilled in the art can select it according to actual needs. Preferably, the volume ratio of the first solvent to the silane coupling agent containing terminal amino groups is 15-20:1.
[0068] In the present invention, halogen atoms are introduced into the surface of the product obtained in step (2) by using acyl halide.
[0069] According to a preferred embodiment of the present invention, the step (3) comprises: first dispersing the product obtained in step (2) and the base in a second solvent, and then mixing with the acyl halide. The present invention has a wide range of selection for the second solvent, as long as the components can be fully dispersed. Preferably, the second solvent is dichloromethane and / or chloroform.
[0070] According to the present invention, preferably, the acyl halide is selected from at least one of acyl fluoride, acyl chloride and acyl bromide, preferably acyl bromide; preferably, the acyl halide contains at least two halogen atoms, preferably, the acyl halide is selected from 2-bromoisobutyryl bromide (BiBB).
[0071] Preferably, the mass ratio of the amount of the acyl halide to the product obtained in step (2) is 0.7-1.2:1, for example, it can be 0.7:1, 0.8:1, 0.9:1, 1:1, 1.1:1, 1.2:1 and other typical but non-limiting ratios, and more preferably 0.9-1:1.
[0072] According to the present invention, when the acyl halide reacts with the product obtained in step (2), hydrogen halide is generated, and the hydrogen halide is stabilized by the introduced base, thereby promoting the forward progress of the reaction. The present invention has a wide range of selection for the type of the base, as long as it can play the role of the above-mentioned acid binding agent. Preferably, the base in step (3) is an aliphatic amine compound, preferably at least one of ethylamine, n-butylamine, mono-n-propylamine, di-n-propylamine, tri-n-propylamine, triethylamine, ethylenediamine and hexamethylenediamine, more preferably triethylamine.
[0073] According to the present invention, preferably, the mass ratio of the amount of the base to the product obtained in step (2) is 0.05-0.2:1, preferably 0.08-0.15:1.
[0074] According to the present invention, preferably, the surface functionalization treatment in step (3) is carried out in the presence of a third solvent. Preferably, the third solvent is 1,4-dioxane.
[0075] Preferably, the conditions for the surface functionalization treatment include: a temperature of -10°C to 10°C, for example, typical but non-limiting temperatures such as -10°C, -8°C, -6°C, -4°C, -2°C, 0°C, 2°C, 4°C, 6°C, 8°C, 10°C, etc., and a time of 18-32h, for example, typical but non-limiting times such as 18h, 20h, 22h, 24h, 26h, 28h, 30h, 32h, etc.
[0076] According to the present invention, in step (4), in the presence of a catalyst, light-induced atom transfer radical polymerization technology is used to prepare a modified barium titanate with a core-shell structure, which can controllably and stably prepare a modified barium titanate coated with a polymer shell containing epoxy groups.
[0077] According to some preferred embodiments of the present invention, in step (4), the temperature of the reaction conditions is 60-90°C, preferably 70-80°C.
[0078] Preferably, the light-inducing conditions in step (4) are provided by ultraviolet light irradiation. Preferably, the conditions of ultraviolet light irradiation include: the ultraviolet light wavelength is 254-400nm, and the irradiation time is 10-20h.
[0079] The monomer of the polymer containing epoxy groups refers to a substance that can obtain the polymer containing epoxy groups through a polymerization reaction. The definition scope of the polymer containing epoxy groups is the same as described above and will not be repeated here.
[0080] In the present invention, any catalyst that is conducive to light-induced atom transfer radical polymerization can be applied to the present invention. Preferably, the catalyst includes a metal-based catalyst and a ligand. The above preferred embodiment is used to obtain a modified barium titanate with a suitable grafting amount within a certain period of time, avoiding the post-processing problem of using too much metal catalyst.
[0081] Preferably, the metal-based catalyst is selected from one of a Cu(I) catalyst, a Cu(II) catalyst and a Fe(III) catalyst. The Cu(I) catalyst refers to a monovalent copper catalyst, and similarly, Cu(II) refers to a divalent copper catalyst, and Fe(III) refers to a trivalent iron catalyst, which are well known to those skilled in the art.
[0082] In some preferred embodiments of the present invention, the metal-based catalyst is CuBr.
[0083] Preferably, the ligand is selected from at least one of tris[2-(dimethylamino)ethyl]amine, pentamethyldiethylenetriamine and 2,2-bipyridine, and more preferably 2,2-bipyridine.
[0084] According to the present invention, preferably, in step (4), the mass ratio of the product obtained in step (3), the catalyst, and the ligand is 1: (0.05-0.18): (0.1-0.36): (1-3), preferably 1: (0.1-0.13): (0.2-0.26): (1.5-2.5). In the above preferred case, it is conducive to obtaining a modified barium titanate with a suitable grafting amount.
[0085] In the present invention, preferably, the hydroxylation treatment, silanization treatment, surface functionalization treatment and graft polymerization reaction can each independently include solid-liquid separation, washing and drying steps. The present invention has no special restrictions on the operation mode and specific conditions of the solid-liquid separation, washing and drying, and can be carried out in a conventional manner in the art, as long as the solvent and unreacted raw materials that may be present in the product can be removed. Preferably, the drying is carried out under vacuum conditions.
[0086] According to a preferred embodiment of the present invention, a method for providing a dispersion comprising a matrix material, a filler and an organic solvent comprises: mixing the matrix material and the filler with an organic solvent respectively to obtain a polymer solution and a filler dispersion, and then mixing the polymer solution with the filler dispersion.
[0087] According to some preferred embodiments of the present invention, the amounts of the matrix material and filler are such that, in the prepared composite dielectric material, the filler content is 5-20wt%, preferably 10-15wt%; the matrix material content is 80-95wt%, preferably 85-90wt%.
[0088] Preferably, the mixing is performed under stirring and / or ultrasonic conditions.
[0089] In the present invention, the film-casting process can be carried out in a conventional manner in the art. Preferably, the film-casting process is carried out at a temperature of 40-60°C.
[0090] Preferably, the drying temperature is 50-55° C., and the drying time is 4-8 hours. Preferably, the drying is performed under vacuum conditions.
[0091] The present invention has no particular limitation on the type and amount of the organic solvent, as long as it can help disperse the matrix material and the filler.
[0092] According to some preferred embodiments of the present invention, the organic solvent is selected from N,N-dimethylformamide and / or dimethyl sulfoxide.
[0093] The third aspect of the present invention provides the use of the composite dielectric material described in the first aspect or the composite dielectric material prepared by the preparation method described in the second aspect in a dielectric capacitor.
[0094] The present invention will be described in detail below through examples.
[0095] In the following preparation examples and embodiments, unless otherwise specified, the raw materials used were commercially available and the room temperature refers to 25°C±5°C.
[0096] In the following preparation examples and embodiments, the content of each component was measured by thermogravimetric analysis.
[0097] The following preparation example is used to illustrate the preparation of modified barium titanate.
[0098] Preparation Example 1
[0099] (1) 10 g of BT nanoparticles with an average particle size of 100 nm and 80 mL of 30 wt% hydrogen peroxide were added to a round-bottom flask, dispersed by ultrasonication for 30 min, and the flask was placed in a 105°C oil bath for condensation and reflux for 4 h. The product was separated by centrifugation at 8000 rpm for 5 min, washed with deionized water for more than 3 times, and dried in a vacuum oven at 80°C for 12 h. The obtained product was recorded as BT-OH.
[0100] (2) 8 g of BT-OH and 4 g of 3-aminopropyltrimethoxysilane (APS) were weighed and added to a 500 mL three-necked flask, and 80 mL of high-purity xylene was added and stirred, and ultrasonicated for 10 min. The mixture was heated to 80 ° C in a N2 atmosphere and reacted for 24 h. After the reaction, the reaction liquid was separated into solid and liquid, and the solid part was washed with deionized water and ethanol in turn until neutral, and then placed in a vacuum oven and dried at 80 ° C for 12 h. The obtained product was recorded as BT-APS.
[0101] (3) 8 g of BT-APS was dispersed in 50 mL of CH2Cl2 solution, and then 1.5 mL of triethylamine was added. The mixture was placed in an ice bath for 3 h to reduce the temperature to 0°C. 2-Bromoisobutyryl bromide (BiBB) was slowly added dropwise for 30 min in an ice bath at 0°C. The ratio of BiBB to BT-APS was 0.9:1. The mixture was reacted in an ice bath for 24 h. The precipitate was washed with a large amount of anhydrous CH2Cl2 and ethanol solvent, and dried in vacuum at 80°C overnight. The product was recorded as BT-Br.
[0102] (4) At room temperature, a polytetrafluoroethylene magnetic stirrer, BT-Br (0.5 g), 1,4-dioxane (3 mL), 60 mg CuBr (CuBr was washed alternately with acetic acid and acetone three times before the experiment and used immediately after drying), 0.13 g 2,2-bipyridine and glycidyl methacrylate (GMA) were added to a 20 mL transparent glass sample bottle in sequence. The mass ratio of BT-Br, CuBr, 2,2-bipyridine and glycidyl methacrylate was 1:0.12:0.26:3. Then, N2 was introduced for a period of time to remove the air in the container. Under ultraviolet light (365 nm), the container was stirred in an oil bath at 70°C for 12 h. After the reaction was completed, the product was washed with tetrahydrofuran and ethanol several times. The product was vacuum dried at 50°C for 24 h. The modified barium titanate obtained was recorded as BT-g-PGMA-1.
[0103] TEM image of BT-g-PGMA-1 Figure 1 As shown, it can be seen that the modified barium titanate has a core-shell structure consisting of a core and an outer shell. The Fourier infrared spectra of the BT-OH, BT-APS, BT-Br, and BT-g-PGMA-1 are shown in Figure 2 According to infrared spectrum test, the infrared spectrum of the modified barium titanate shows that at 910 cm -1 、1720cm -1 The vibration peak appears at 100°, proving that BT is successfully grafted onto PGMA. The thermogravimetric curve (TG) of BT-g-PGMA-1 is shown in Figure 3According to the thermogravimetric curve, the weight percentage of the core is 84% of the modified barium titanate, the weight percentage of the shell is 16%, the content of small molecule segments in the shell is about 22.5%, and the PGMA content is 77.5%.
[0104] Preparation Example 2
[0105] According to the method of Preparation Example 1, the difference is that, at room temperature, polytetrafluoroethylene magnetic stirring bar, BT-Br (0.5g), 1,4-dioxane (3mL), 60mg CuBr (CuBr was washed alternately with acetic acid and acetone three times before the experiment and used immediately after drying), pentamethyldiethylenetriamine (PMDETA) and glycidyl methacrylate (GMA) were added to a 20mL transparent glass sample bottle in sequence, and then N2 was introduced for a period of time to remove the air in the container, and stirred in an oil bath at 70°C under ultraviolet light (365nm) for 12h. The mass ratio of BT-Br, CuBr, PMDETA and glycidyl methacrylate was 1:0.12:0.144:3. The reaction was carried out for 12h under magnetic stirring and ultraviolet light (365nm). After the reaction was completed, the product was washed with tetrahydrofuran and ethanol several times. The product was vacuum dried at 50°C for 24h, and the modified barium titanate obtained was recorded as BT-g-PGMA-2.
[0106] TEM images of BT-g-PGMA-2 and Figure 1 Similarly, it has a core-shell structure consisting of a core and a shell. The Fourier infrared spectrum of BT-g-PGMA-2 is similar to Figure 2 Similarly, BT surface was grafted with PGMA.
[0107] Thermogravimetric analysis showed that the core accounted for 79% of the total weight of the modified barium titanate, the weight percentage of the shell was 21%, the content of the small molecule segment used to connect the polymer and the barium titanate in the shell was 17.1%, and the content of PGMA was 82.9%.
[0108] Preparation Example 3
[0109] The method of Preparation Example 1 was followed, except that in step (4), the mass of glycidyl methacrylate was 0.5 g, and the mass ratio of BT-Br, CuBr, 2,2-bipyridine and glycidyl methacrylate was 1:0.12:0.26:1. The obtained modified barium titanate was designated as BT-g-PGMA-3. The composition is shown in Table 1.
[0110] TEM images of BT-g-PGMA-3 and Figure 1Similarly, it has a core-shell structure consisting of a core and an outer shell, and the Fourier infrared spectrum is similar to that of Preparation Example 1, indicating that PGMA is grafted on the surface of BT. Through thermogravimetric analysis, the barium titanate core accounts for 89% of the total weight of the modified barium titanate, the weight percentage of the outer shell is 11%, the content of the small molecule segment used to connect the polymer and the barium titanate in the outer shell is 32.7%, and the content of PGMA is 67.3%.
[0111] Comparative Preparation Example 1
[0112] The method of Preparation Example 1 is followed, except that in step (4), an equal amount of methyl methacrylate (MMA) is used to replace glycidyl methacrylate.
[0113] The obtained modified barium titanate is recorded as BT-g-PMMA. Thermogravimetric analysis shows that the core accounts for 74.5% of the total weight of the modified barium titanate, the weight percentage of the shell is 25.5%, the content of the small molecule segment used to connect the polymer and the barium titanate is 14.1%, and the content of PMMA is 85.9%.
[0114] The following examples are used to illustrate the preparation of composite dielectric materials.
[0115] Example 1
[0116] 0.2 g of cyanoethyl cellulose (substitution degree is 2) was dissolved in 10 mL of DMF and magnetically stirred until completely dissolved. The modified barium titanate BT-g-PGMA-1 prepared in Preparation Example 1 was added to 4 mL of DMF and ultrasonically dispersed for 1 h according to the mass of filler: the total mass of matrix and filler being 0.05:1 to obtain a filler dispersion.
[0117] The dissolved polymer solution was added to the filler dispersion and then magnetically stirred for 10 hours; the mixed solution was placed in a water bath for ultrasonic treatment for 0.5 hours; the solution was then cast on the surface of a clean glass sheet by a casting method; it was dried on a 50°C flat heating table for 5 hours, and then dried in a 50°C vacuum drying oven for 12 hours. The obtained composite dielectric material was recorded as A1.
[0118] Examples 2-7, Comparative Example 1
[0119] The method of Example 1 is followed, except that the amounts and selections of fillers and matrix materials are as shown in Table 1.
[0120] Comparative Example 2
[0121] 0.2 g of cyanoethyl cellulose (substitution degree 2) was dissolved in 10 mL of DMF and magnetically stirred until completely dissolved. Unmodified barium titanate was added to 4 mL of DMF and ultrasonically dispersed for 1 h according to the mass of filler: total mass of matrix and filler of 0.1:1 to obtain a filler dispersion.
[0122] The dissolved polymer solution was added to the filler dispersion and then magnetically stirred for 10 hours; the mixed solution was placed in a water bath for ultrasonic treatment for 0.5 hours; the solution was then cast on the surface of a clean glass sheet by a casting method; it was dried on a 50°C flat heating table for 5 hours, and then dried in a 50°C vacuum drying oven for 12 hours to obtain a BT / CEC composite film.
[0123] Comparative Examples 3-5
[0124] The method of Comparative Example 2 is followed, except that the amounts of filler and base material used are as shown in Table 1.
[0125] Table 1
[0126]
[0127] The dielectric properties of the composite dielectric materials prepared in the above examples and comparative examples were tested.
[0128] Test method: Use a vacuum coating machine to sputter silver electrodes with a thickness of 50nm and a diameter of 1cm on both sides of the prepared film. Use an E4980AL-102 LCR tester to apply currents of different frequencies at both ends of the electrodes at room temperature and measure the 10 2 -10 6 Dielectric constant and loss in Hz.
[0129] The energy storage density and breakdown strength were measured using a ferroelectric tester model Premiere II from Radiant Technologies. The thin film silver electrode used in the ferroelectric tester has a thickness of 50nm and a diameter of 0.1cm. At room temperature, currents of different electric field strengths at a certain frequency were applied to both ends of the electrode to measure the energy storage density and film breakdown strength under different electric field strengths.
[0130] The dielectric constant curves of the composite dielectric materials obtained in Examples 1-4 are shown in Figure 4 (a) Dielectric loss curve Figure 4 (b), the dielectric constant curves of the composite dielectric materials obtained in Comparative Examples 2-5 are shown in Figure 4 (c) Dielectric loss curve Figure 4 (d) By Figure 4 It can be seen that compared with comparative examples 2-5, the composite dielectric materials prepared in examples 1-4 have higher dielectric constants, and the dielectric loss at low frequencies is greatly reduced, indicating that the material effectively suppresses the dielectric loss.
[0131] The energy storage density and charge-discharge efficiency curves of the composite dielectric materials prepared in Examples 1-4 are shown in FIG. Figure 5 (a), the energy storage density and charge-discharge efficiency curves of the composite dielectric materials prepared in Comparative Examples 2-5 are shown in Figure 5(b) By Figure 5 It can be seen that compared with comparative examples 2-5, the composite dielectric materials prepared in embodiments 1-4 have overall higher charge and discharge efficiency and higher breakdown strength within the above-mentioned electric field strength range, indicating that the nanocomposite film incorporating modified fillers improves the interface performance and inhibits the generation of leakage current, thereby greatly improving the breakdown strength and energy storage density.
[0132] The dielectric loss of the composite dielectric material prepared in Comparative Example 1 at 100 Hz is as high as 1.1.
[0133] Example 5 uses highly substituted cyanoethyl cellulose and dimethyl sulfoxide (DMSO) as solvents. The dielectric loss of the 10wt% film at 100Hz is 0.55, and the dielectric constant is 25.7. Compared with Example 1, the use of a high-polarity solvent slightly reduces the dielectric constant of the composite material and enhances the dipole relaxation polarization. Since the dipole does not have enough time to move or rotate at high frequencies, it causes molecular friction, thereby increasing the dielectric loss.
[0134] The composite dielectric material prepared in Example 6 has a loss of 0.6 at 100 Hz and a dielectric constant of 28. Compared with Example 2, the dielectric loss of the material has increased, which may be due to the excessive number of coated polymer shells. The shells are thick and the filler has high hardness, which leads to poor dispersion in the matrix. The shells between different particles are easily bonded together, affecting its ability to inhibit charge migration.
[0135] The composite dielectric material prepared in Example 7 has a loss of 0.9 at 100 Hz and a dielectric constant of 30. This may be because there is less PGMA and it is unable to form a sufficient cross-linking network, so the effect of suppressing the generation of leakage current between interfaces is slightly poor, thereby increasing the accumulation of charge at the interface.
[0136] It can be seen from the above embodiments and comparative examples that the present invention modifies the surface of barium titanate, coats the surface of barium titanate with a polymer shell layer containing epoxy groups, and composites the obtained modified filler with a cyanoethyl cellulose matrix to obtain a composite dielectric material. Since the epoxy groups in the outer shell of the modified filler can form a covalent cross-linked network with the hydroxyl groups on the surface of cellulose as an electron potential well to inhibit the migration of carriers, compared with comparative examples 1-5, the composite dielectric material provided by the present invention has a higher dielectric constant. In a preferred case, it can take into account both a higher dielectric constant and a lower dielectric loss, excellent breakdown strength and energy storage density.
[0137] The preferred embodiments of the present invention are described in detail above, but the present invention is not limited thereto. Within the technical concept of the present invention, the technical solution of the present invention can be subjected to a variety of simple modifications, including the combination of various technical features in any other suitable manner, and these simple modifications and combinations should also be regarded as the contents disclosed by the present invention and belong to the protection scope of the present invention.
Claims
1. A composite dielectric material, characterized in that: The composite dielectric material comprises a filler and a matrix material, wherein the filler is modified barium titanate and the matrix material is cyanoethyl cellulose; The modified barium titanate comprises a barium titanate core and a shell, wherein the shell comprises a polymer containing epoxy groups, and the core and shell are connected by covalent bonds. According to infrared spectrum test, the infrared spectrum of the modified barium titanate has a peak at 910±10cm -1 、1720±10cm -1 There are characteristic peaks of epoxy group and carbonyl group respectively.
2. The composite dielectric material according to claim 1, wherein: Based on the total mass of the modified barium titanate, the content of the shell is 5-20wt%, preferably 10-18wt%; the content of the barium titanate core is 80-95wt%, preferably 82-90wt%; Preferably, the shell further comprises a small molecule segment, and the small molecule segment is used to connect the barium titanate and the polymer containing the epoxy group. Preferably, the small molecule segment is selected from the residue of a silane coupling agent containing an amino group at the end and / or the residue of an acyl bromide; Preferably, in the shell, the content of the small molecule chain segment does not exceed 35wt%, preferably 18-30wt%; the content of the polymer containing epoxy groups is not less than 65wt%, preferably 70-82wt%.
3. The composite dielectric material according to claim 1 or 2, wherein: The polymer containing epoxy groups is polyglycidyl methacrylate; Preferably, the average particle size of the barium titanate is 10-100 nm, preferably 80-100 nm.
4. The composite dielectric material according to any one of claims 1 to 3, wherein: The degree of substitution of the cyanoethyl cellulose is 2-2.8, preferably 2-2.6; Preferably, based on the total mass of the composite dielectric material, the content of the filler is 5-20wt%, preferably 10-15wt%; the content of the matrix material is 80-95wt%, preferably 85-90wt%.
5. A method for preparing a composite dielectric material, characterized in that: include: Providing a dispersion liquid including a matrix material, a filler and an organic solvent, and then casting the dispersion liquid into a film and drying it; The filler is modified barium titanate, and the matrix material is cyanoethyl cellulose; The modified barium titanate comprises a barium titanate core and a shell, wherein the shell comprises a polymer containing epoxy groups, and the core and shell are connected by covalent bonds. According to infrared spectrum test, the infrared spectrum of the modified barium titanate has a peak at 910±10cm -1 、1720±10cm -1 There are characteristic peaks of epoxy group and carbonyl group respectively.
6. The preparation method according to claim 5, wherein: The preparation method of the modified barium titanate comprises: (1) hydroxylating barium titanate; (2) mixing the product obtained in step (1), a silane coupling agent containing a terminal amino group and a first solvent, and performing a silanization treatment; (3) mixing the product obtained in step (2), an acyl halide and a base, and performing a surface functionalization treatment on the product obtained in step (2); (4) under light-induced conditions and in the presence of a catalyst, mixing the product obtained in step (3) with a polymer monomer containing an epoxy group to carry out a reaction, wherein the reaction includes a grafting reaction and a polymerization reaction; Preferably, the polymer monomer containing epoxy groups is glycidyl methacrylate.
7. The preparation method according to claim 6, wherein: The hydroxylation treatment in step (1) comprises: mixing barium titanate with hydrogen peroxide and performing a hydroxylation treatment; Preferably, the temperature of the hydroxylation treatment is 80-120°C and the time is 2-8h; Preferably, the mass ratio of the hydrogen peroxide to the barium titanate is 8-10:1; Preferably, the concentration of the hydrogen peroxide is 20-40wt%, preferably 25-35wt%; Preferably, the average particle size of the barium titanate is 10-100 nm, preferably 80-100 nm.
8. The preparation method according to claim 6 or 7, wherein: The silane coupling agent containing terminal amino groups is selected from 3-aminopropyltrimethoxysilane and / or 3-aminopropyltriethoxysilane; Preferably, in step (2), the temperature of the silanization treatment is 50-100°C, preferably 70-90°C; the time is 12-48h, preferably 20-30h; Preferably, the silanization treatment is carried out under a protective atmosphere, and the protective atmosphere is provided by at least one of nitrogen, argon and neon; Preferably, the mass ratio of the product obtained in step (1) to the silane coupling agent containing terminal amino groups is 1-3.5:1, preferably 2-2.5:1; Preferably, the volume ratio of the first solvent to the silane coupling agent containing terminal amino groups is 15-20:
1.
9. The preparation method according to any one of claims 6 to 8, wherein: The acyl halide is selected from at least one of acyl fluoride, acyl chloride and acyl bromide, preferably acyl bromide; Preferably, the acyl halide is 2-bromoisobutyryl bromide; Preferably, the mass ratio of the amount of the acyl halide to the product obtained in step (2) is 0.7-1.2:1, preferably 0.9-1:1; Preferably, the base in step (3) is an aliphatic amine compound, preferably at least one of ethylamine, n-butylamine, mono-n-propylamine, di-n-propylamine, tri-n-propylamine, triethylamine, ethylenediamine and hexamethylenediamine, more preferably triethylamine; Preferably, the mass ratio of the base to the product obtained in step (2) is 0.05-0.2:1; Preferably, the conditions for the surface functionalization treatment include: a temperature of -10°C to 10°C and a time of 18-32 hours.
10. The preparation method according to any one of claims 6 to 9, wherein: The light-inducing condition in step (4) is provided by ultraviolet light irradiation; Preferably, the conditions of ultraviolet light irradiation include: ultraviolet light wavelength is 254-400nm, irradiation time is 10-20h; Preferably, the temperature of the reaction conditions is 60-90°C, preferably 70-80°C; Preferably, the catalyst comprises a metal-based catalyst and a ligand; Preferably, the metal-based catalyst is selected from one of a Cu(I) catalyst, a Cu(II) catalyst and a Fe(III) catalyst, preferably CuBr; Preferably, the ligand is selected from at least one of tris[2-(dimethylamino)ethyl]amine, pentamethyldiethylenetriamine and 2,2-bipyridine, and more preferably 2,2-bipyridine; Preferably, in step (4), the mass ratio of the product obtained in step (3), the metal-based catalyst, the ligand and the polymer monomer containing epoxy groups is 1: (0.05-0.18): (0.1-0.36): (1-3).
11. The preparation method according to any one of claims 5 to 10, wherein: The amounts of the matrix material and the filler are such that, in the composite dielectric material, the content of the filler is 5-20wt%, preferably 10-15wt%; the content of the matrix material is 80-95wt%, preferably 85-90wt%; Preferably, the temperature of the film casting is 40-60°C; Preferably, the drying temperature is 50-55° C. and the drying time is 4-8 hours.
12. Use of the composite dielectric material according to any one of claims 1 to 4 or the composite dielectric material obtained by the preparation method according to any one of claims 5 to 11 in a dielectric capacitor.
Citation Information
Patent Citations
Cyanoethyl cellulose based high-dielectric flexible nano-composite film and preparation method thereof
CN104672502A
High-energy-storage barium strontium titanate / PVDF-based polymer composite material and preparation method thereof
CN115109376A
Improved electroluminescent device
GB9204705D0
Dielectric composition and dispersion-type electric field luminous element
JP1990309593A
Polymeric piezoelectric material comprising polylactic acid based resin and inorganic compound
JP2005213376A
Cited By
Biomass-based supramolecular composite film as well as preparation method and application thereof
CN122404810A
A biomass-based supramolecular composite thin film, its preparation method and application
CN122404810B